Posthuman Creativity Labs: Artificial Intelligence and Blockchain in Music (guest teacher at Creative Performance Labs, additional course) - Łukawski, Adam; Guest Teaching Posthuman Creativity Labs at the Creative Performance Labs course Conservatorium van Amsterdam 29/01/2024, 30/01/2024, 12/02/2024, 13/02/2024 (Amsterdam, The Netherlands Conservatorium van Amsterdam, 2024)
The focus of this course is on how existing AI (Artificial Intelligence) and blockchain tools canenhance the creative capabilities of a musician today and how does this change the creativepractices that we know. The aim is to provide to participants the basic knowledge about the newparadigms of (digital) art creation and dissemination and to navigate them towards the digital toolsenabling post-human creativity to become part of their own artistic practice. Some of the questionsthat the course strives to answer are: how can human creativity be enhanced by ArtificialIntelligence? What are the good techniques for music composition with AI and blockchain? How isthe definition of a work of art different today than 300 years ago and 100 years ago? What is thepurpose of decentralised music? What is the agency of the work of art in the post-human era? Canthe work of art posses itself?
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music